2017
DOI: 10.2147/ott.s138595
|View full text |Cite
|
Sign up to set email alerts
|

Primary lung sarcoma treated with stereotactic ablative radiotherapy: a case report

Abstract: Primary lung sarcoma (PLS) is an extremely rare, very aggressive malignancy. Surgical removal is considered the treatment of choice, and patients who have been given conventional radiotherapy have had inferior outcomes. This study is the first describing a case of PLS treated with stereotactic ablative radiotherapy (SABR), which precisely targets a small tumor with a markedly higher biologically effective dose than conventional radiotherapy. The patient was an 82-year-old man who was diagnosed with primary lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 32 , 33 In a large retrospective analysis based on the SEER database, Spraker et al 16 described that the 5-year survival rates of PPS patients receiving surgery alone, radiotherapy alone, surgery and radiotherapy were 41%, 7%, and 25%, respectively. Yeo et al 12 reported the effect of ‘stereotactic ablation radiotherapy’ (SABR) for treating PPS. The results showed that SABR achieved excellent local control with minimal toxicity in both extrapulmonary metastatic sarcoma and PPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 , 33 In a large retrospective analysis based on the SEER database, Spraker et al 16 described that the 5-year survival rates of PPS patients receiving surgery alone, radiotherapy alone, surgery and radiotherapy were 41%, 7%, and 25%, respectively. Yeo et al 12 reported the effect of ‘stereotactic ablation radiotherapy’ (SABR) for treating PPS. The results showed that SABR achieved excellent local control with minimal toxicity in both extrapulmonary metastatic sarcoma and PPS.…”
Section: Discussionmentioning
confidence: 99%
“…Five-year OS rate pertinent to PPS is influenced by several factors including patient age, tumor size, surgery, metastasis, degree of histological malignancy, and therapeutic modalities. 2 , 11 , 12 Tumor prognosis can be accurately predicted using nomograms. Data pertinent to PPS patients procured from the registry of ‘Surveillance, Epidemiology, and End Results (SEER) program database’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of incomplete resection or prior inoperability, adjuvant or palliative radio- and chemotherapy are recommended, although survival benefit has not been established for these treatment modalities [ 1 3 ]. Recently, stereotactic ablative radiotherapy has been suggested to be a valuable alternative for surgery for small lesions in medically inoperable patients, although robust evidence is still lacking [ 15 ]. Results of conventional radiotherapy appear to be inferior.…”
Section: Discussionmentioning
confidence: 99%